Behavioral and Sociodemographic Risk Factors of High Blood Pressure Among Community in Medan City - Fazidah Aguslina Siregar; Asfriyati Asfriyati (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
High blood pressure, or hypertension, is a worldwide health issue. The prevalence of hypertension is still high today. However, there are no established risk factors for hypertension. The purpose of this study was to identify risk factors for hypertension. This study used a cross-sectional design and was observational. The sample included 200 recruits that were purposively selected from 4 subdistricts in Medan city. Data were collected through interviews and made measurements. Data were analyzed using simple and multiple logistic regression. Prevalence of high blood pressure was 59.0%, consisting of pre hypertension at 24.5% and hypertension at as much as 34.5%. The majority of respondents were aged 45 years or younger (66.0%), 185 were female (92.5%), 124 were low income (62.0%), 143 had no family history (71.5%), 95 were overweight (47.5%), 137 were normal blood glucose, 183 had no smoking habit (91.5%), and 134 were physically inactive (67,0%). The Multiple Logistic regression showed that age, Basal metabolic index, daily vegetables, and fruit consumption are significant factors that contribute to high blood pressure in the community in Medan City. Age, BMI and daily vegetables and fruit consumption are significant factors with high blood pressure among community. Intervention programs should be primarily focused on risk factors such as losing weight and maintaining an ideal body weight and implementing healthy lifestyle. Keyword: High blood pressure, Prevalence, Determinant